2021
DOI: 10.1155/2021/1604245
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Substance Use and Its Associated Factors among Truck Drivers in Ethiopia

Abstract: Background. Road traffic accidents (RTAs) remain an important public health issue worldwide. Psychoactive substance use is one of the main contributors to the occurrence of traffic accidents, and its use by truck drivers is a global problem. Also, psychoactive substance use is a commonly observed behavior among truck drivers. To the best of our knowledge, no evidence shows the prevalence and factors associated with psychoactive substance use among truck drivers in Ethiopia. Therefore, this study was aimed at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 23 publications
3
21
1
1
Order By: Relevance
“…Substance use (alcohol drinking/khat chewing): consuming any substance (alcohol or khat) within the last 1 month/30 days ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Substance use (alcohol drinking/khat chewing): consuming any substance (alcohol or khat) within the last 1 month/30 days ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Current substance use: consuming any substance (Alcohol, Khat and cigarettes smoking) within the last 1 month/30 days ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, there was a signi cant association between ethnicity, religion, monthly income, knowledge, perception, and psychoactive substance abuse in the current study. Previous studies conducted in Nigeria and Ethiopia have also shown religion, age, and marital status as sociodemographic variables in uencing the abuse of psychoactive substances among commercial drivers [2,21]. Drivers who were Islamic religious followers were ve times more likely to use psychoactive substances than those practicing Christianity.…”
Section: Discussionmentioning
confidence: 82%